Evaluating the mental and emotional effects of Sahand Bonab thermal power plant greenhouse on rural communities, Case study: Rurlas in Bonab - Mohamad Zaheri; Ali Majnouni-Toutakhane (تحقیقات کاربردی علوم جغرافیایی)
The increased use of thermal power plants has led to the spread of greenhouse gases in the air and has caused psychological problems for humans. Accordingly, the present study was conducted to measure the pollutants released by Sahand Bonab thermal power plant and to investigate the effects of this pollution on the psychological and psychological pressure of rural residents. The GWP100 method was used to measure the pollutants of the power plant and to measure the mental and emotional pressures of the citizens, a questionnaire was used to assess the psychological stress of Markham. The statistical population of this study is 10254 people over 15 years of age in 7 villages located in the greenhouse of the power plant. Using formulas and simple random sampling, 375 subjects were selected as sample size. The results showed that the most pollutants released are CO2 and NOx, which is 4.17 times the warm seasons in the seasons. Also, analysis of the results by using a Pearson test showed that six variables including neurological and disturbing variables p= 0.272, stress and psychological stress p= 0.325, feeling of energy decrease, p= 0.287, feeling of despair and disappointment in life p = 0.142, feeling Depression in life of p= 0.211 and change in behavior patterns in everyday life p= 0.269 had the most effect on air pollution. Also, mental and psychological stress in nearby villages was higher than in remote villages, more women than young men than older men and elderly people. The results of multivariate regression and path analysis showed that in general, the air pollution caused by the power plant has the ability to explain R2 = 37.42 percent of the changes related to the psychological and psychological pressure of the villagers. Finally, it can be said that thermal power plants have negative mental and psychological effects according to type of activity, type of age and gender of the villagers, which should be considered in the studies of the construction of power plants.